Analisis Pengaruh kemiskinan, pertumbuhan penduduk, dan Pertumbuhan Ekonomi terhadap Indeks Pembangunan Manusia di Provinsi Jawa Timur tahun 2015 – 2023 - Wahyu Hidayat; Wahyudi; Adam Ramadhan (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research focuses on Population Growth, Human Development Index Level and Poverty Level in Economic Growth in East Java Province. Proper human development will enable the maximization of production factors, so HDI is considered to play an important role in contemporary economic development planning. The research method used, namely a certain type of quantitative research, was used in this research. Meanwhile, the methodology used in this research is a quantitative descriptive approach for research that tries to describe or characterize numbers that have been processed according to certain standards—not a qualitative descriptive methodology. The location of this research was carried out in East Java Province, whose capital is the city of Surabaya through the Central Statistics Agency (BPS) of East Java Province, while at that time the research was carried out in the XIV semester of 2023. The data collection methods used in this research were documentation and field studies. Regression analysis using panel data and the Eviews 9 program is the analysis method used in this research. The research results in this study are that the Poverty variable only has a negative and significant effect on HDI, which means that if the amount of poverty increases, the HDI value will also decrease, while for the variables Economic Growth Rate and Population Growth both have a significant positive effect on HDI, meaning that if As economic and population growth rates increase, the HDI value will also increase.